Nursing student–nurse teacher cooperation using mobile technology during the clinical practicum - Strandell-Laine, Camilla (fi=Turun yliopisto|en=University of Turku|, 2019)
The purpose of this three-phase study was to describe the use of mobile devices in nursing student–nurse teacher cooperation during the clinical practicum, to develop a novel alternative called mobile cooperation intervention (MCI) for this cooperation and to evaluate its effectiveness on the students’ clinical learning outcomes and acceptability from the perspective of nursing students. The ultimate goal is to improve the quality of nursing education and thus the outcomes of patient care. In Phase I, an integrative review of use of the mobile devices in nursing student–nurse teacher cooperation during the clinical practicum was conducted. In Phase II, the CLES+T scale was further developed. Additionally, a mobile application called Study@CampusPro (App) and a mobile cooperation intervention (MCI) were developed. In Phase III, a randomised controlled trial design was used to evaluate the effectiveness of the MCI on nursing students’ clinical learning outcomes, i.e. the individual outcomes (competence and self-efficacy) and contextual outcomes (quality of the clinical learning environment). Data were collected using three instruments (1) the Nurse Competence Scale (NCS), (2) the Self-efficacy in Clinical Performance instrument (SECP) and (3) the Clinical Learning Environment, Supervision and Nurse Teacher scale (CLES+T2). Eligible nursing students (n=102) were randomly allocated to an intervention group (n=52) with mobile cooperation and a control group (n=50) with standard cooperation. The congruence between the nursing students’ self-assessed competence and the mentors’ assessments of the students’ competence was examined by comparing the nursing students’ self-assessments and their mentors’ (n=95) assessments. Moreover, a process evaluation was conducted by examining the students’ acceptability of the MCI by using a process evaluation questionnaire (Peq) developed for this study and the System Usability Scale (SUS) and student essays. The methods of analysis used in this study were critical appraisal, thematic and content analysis as well as descriptive statistics and statistical modelling. There have been only a few studies (n=17) on nursing student–nurse teacher mobile cooperation and their methodological weaknesses are evident. The MCI was found to be significantly effective in facilitating nursing student–nurse teacher cooperation and as effective as standard cooperation in improving the clinical learning outcomes of nursing students. The older age was shown to be significantly associated with improvements in the competence in the whole study population. Students’ self-assessed theoretical knowledge and practical skills prior to the clinical practicum were also shown to be significantly associated with the quality experienced of the clinical learning environment. In the control group, the students’ self-assessed competence showed a weak but significant congruence with their mentors’ assessments. The MCI was given a high degree of acceptance among students and the App’s usability was rated as rather good. The items developed for the T -subscale of the CLES+T scale, on which the CLES+T2 scale were based, demonstrated an appropriate level of content validity and good internal consistency. This study suggests there is potential in the MCI to improve the quality of the nurse teacher’s pedagogical cooperation with students and for being used as an alternative cooperation method in supporting students’ clinical learning outcomes.

Hoitotyön opiskelijan ja opettajan välinen mobiiliteknologia-avusteinen ohjaus harjoittelun aikana Tämän kolmivaiheisen tutkimuksen tarkoituksena oli kuvata mobiililaitteiden käyttöä opiskelijan ja opettajan välisessä harjoittelun aikaisessa ohjauksessa, kehittää mobiiliohjausinterventio (MCI) tähän ohjaukseen ja arvioida intervention vaikuttavuutta opiskelijan kliinisiin oppimistuloksiin ja intervention hyväksyttävyyttä opiskelijoiden näkökulmasta. Tutkimuksen tavoitteena on edistää hoitotyön koulutuksen laatua ja siten hoitotyön tuloksia. Vaiheessa I tehtiin integratiivinen katsaus mobiililaitteiden käytöstä hoitotyön opiskelijan ja opettajan välisessä harjoittelun aikaisessa ohjauksessa. Vaiheessa II jatkokehitettiin kliininen oppimisympäristö, ohjaus ja opettaja (CLES+T) -mittaria sekä kehitettiin mobiiliapplikaatio Study@CampusPro (App) ja mobiiliohjausinterventio (MCI). Vaiheessa III toteutettiin satunnaistettu kontrolloitu tutkimus, jossa mitattiin mobiiliohjausintervention vaikuttavuutta hoitotyön opiskelijoiden kliinisiin oppimistuloksiin, yksilösidonnaisiin (kompetenssi ja minäpystyvyys) ja kontekstisidonnaisiin (kliinisen oppimisympäristön laatu) seuraavilla mittareilla: (1) Sairaanhoitajien ammattipätevyysmittari (NCS), (2) Self-efficacy in Clinical Performance (SECP) -mittari ja (3) CLES+T2 -mittari. Tutkimukseen soveltuvat hoitotyön opiskelijat (n=102) satunnaistettiin mobiiliohjausta saavaan interventioryhmään (n=52) ja standardiohjausta saavaan kontrolliryhmään (n=50). Opiskelijoiden kompetenssin itsearviointien vastaavuutta ohjaajien arvioimaan opiskelijoiden kompetenssiin tarkasteltiin vertaamalla opiskelijoiden itsearviointeja ohjaajien (n=95) arviointeihin. Lisäksi toteutettiin prosessievaluaatio, jossa selvitettiin opiskelijoiden mobiiliohjausintervention hyväksyttävyyttä tätä tutkimusta varten kehitetyllä prosessievaluaatiokyselyllä (Peq), SUS -mittarilla ja opiskelijoiden esseillä. Analyysimenetelminä olivat kriittinen arviointi, temaattinen ja sisällön analyysi sekä kuvailevat tilastolliset menetelmät ja tilastollinen mallintaminen. Mobiililaitteiden käytöstä hoitotyön opiskelijan ja opettajan välisessä harjoittelun aikaisessa ohjauksessa on rajoitetusti aikaisempia tutkimuksia (n=17) ja niissä on havaittavissa menetelmällisiä heikkouksia. Mobiiliohjausinterventio osoittautui tehokkaaksi menetelmäksi hoitotyön opiskelijan ja opettajan välisessä harjoittelun aikaisessa ohjauksessa sekä yhtä tehokkaaksi edistämään opiskelijoiden kliinisiä oppimistuloksia kuin standardiohjaus. Opiskelijan korkeammalla iällä ja kompetenssin kasvulla oli merkitsevä yhteys koko tutkimuspopulaatiossa. Opiskelijoiden itsearvioimilla teoreettisilla tiedoilla ja käytännön taidoilla ennen harjoittelua sekä koetulla kliinisen oppimisympäristön laadulla oli merkitsevä yhteys. Kontrolliryhmässä oli heikko vastaavuus opiskelijoiden ja ohjaajien arvioiman opiskelijoiden kompetenssin välillä. Mobiiliohjausinterventio oli erittäin hyväksyttävä ja mobiiliapplikaation käytettävyys oli melko hyvä opiskelijoiden arvioimana. CLES+T -mittariin kehitetyt uudet T2 -osion väittämät, jotka olivat perustana CLES+T2 -mittarille, olivat sisällöllisesti valideja ja johdonmukaisia. Tämä tutkimus osoittaa mobiiliohjausinterventiolla olevan potentiaalia edistää hoitotyön opettajan pedagogisen ohjauksen laatua ja se soveltuu vaihtoehtoiseksi ohjausmenetelmäksi tukemaan opiskelijan kliinisiä oppimistuloksia.